Development and using of advanced manufacturing technology in russian industry - M. A. Miller (Вестник СибАДИ, 2017)
The article comprises the sources and the conditions of development and using of advanced technology in Russian industry. The perspective technological trends for innovative industry development are described and analysed. The special attention is paid to the necessity of the training of qualified specialists for high-technological productions. The future prospects of development and using of advanced technology in Russian industry manufacture are determined.